Analisis Kinerja Pengelolaan Limbah Infeksius Selama Masa Pandemi Covid-19 Studi Kasus di RSUD Kota Depok - Fara Asifa Ulfimora; Zaenal Abidin; Andes Ismayana (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Medical waste management is one of the important things in handling the Covid-19 pandemic. Depok City is one of the areas of West Java Province in Indonesia which in the spread of Covid 19 is in the 5 (five) highest positions. The purpose of this research is the management of infectious waste before and during the emergence of the Covid-19 pandemic. This study used a qualitative method. Stages of research is the identification of performance and assessment of the performance of the management of infectious waste using the Balanced Scorecard method, identification plan management strategies using the SWOT method and prioritizing the implementation of the strategy with the method Interpretative Structural Modeling (ISM). The results showed that the infectious waste generation at the Depok City Hospital during the Covid-19 pandemic increased to 2.75 tons per year. The hospital has made efforts to reduce and sort out, but the obstacles faced during the sorting process are the limited number of Personal Protective Equipment (PPE) so that it can increase the risk of transmitting Covid-19 to officers and the absence of cold storage in the Temporary Disposal of Hazardous and Toxic Materials. (TPS B3). The Depok City Regional General Hospital (RSUD) has collaborated with third parties who have permits from the government. The most influential strategy that can be carried out by hospitals is to improve waste management facilities and infrastructure and strengthen SOPs with waste management parties.